PENGARUH PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VII - Nakhwanisa, Nakhwanisa (Departemen Matematika, 2023)
One of the most important goals in learning mathematics is to understand the concept. In addition, understanding the concept is the foundation when learning mathematics. In fact, the competence of students in class VII SMPN 2 Pulau Punjung in understanding the concept is still lacking. The application of the discovery learning model is one of the strategies that can increase understanding of mathematical concepts. The research was conducted to find out students' understanding of mathematical concepts taught with superior discovery learning models compared to those taught with direct learning models for class VII SMPN 2 Pulau Punjung. This research is a quasi-experimental study using a non-equivalent posttest only control group design. All students in class VII SMPN 2 Pulau Punjung were used as the research population, and the experimental group was class VII.A and the control group was class VII.C. The instrument applied to the research is the final test of understanding the concept in the form of essay questions. From the data analyzed and discussed, it can be concluded that the understanding of the concepts learned through discovery learning is superior to learning in Class VII SMPN 2 Pulau Punjung with the direct learning model. Keywords–Discovery learning, Concept Understanding, Direct Learning, Mathematic